Halal food and Consumer’s Rights in Pakistan: Analytical study - Fareeha Siddiq; Samina Saadia (jihat-ul-islam, 2022)
Consumer rights means right to be protected against the marketing of goods and services, which are hazardous to life and property. Provision of Halal food is the basic rights of a Muslim. The government of Pakistan has made regular legislation on national and provincial level. The prime objective behind conducting this study is to clarify the fact that the rules made for the Halal food industry in Pakistan are entirely followed or not? Although meaning of consumer, consumer rights and the contemporary laws of Pakistan about consumer rights has been explained. A consumer is a king in the market place. The markets are highly competitive with an apple consumer’s choice and they need a greater awareness how to protect their rights.